Through the autumn air [large type] - Irvin, Kelly (Irvin, Kelly. Every Amish season novel., 2018)
The mother of ten and a widow of seven years, Mary Katherine is always willing to step in and help her friends around her Amish community. Now that her last child is married, she pours her abundant creative spirit into writing stories, and dreams of opening a bookstore. The church elders want her to work in an Amish-owned store instead. When an English stranger breaks into her house to make himself a sandwich one autumn night, Mary Katherine turns to her friend Ezekiel. Burke is need of more than a meal, and Ezekiel offers him the job at his restaurant. As Mary Katherine and Ezekiel work together with Burke, can they learn to trust in the hope that comes with each new season?